Cannulation‐related adverse events of peripheral veno‐arterial extracorporeal membrane oxygenation support in heart transplantation: Axillary versus femoral artery cannulation. Issue 3 (18th December 2022) - Ohira, Suguru; Dhand, Abhay; Hirani, Rahim; Martinez, Sabrina; Lanier, Gregg M.; Levine, Avi; Pan, Stephen; Aggarwal‐Gupta, Chhaya; Gass, Alan L.; Wolfe, Kevin; Spielvogel, David; Kai, Masashi
Abstract: Background: In heart transplantation (HT), peripheral veno‐arterial extracorporeal membranous oxygenation (VA‐ECMO) is utilized preoperatively as a direct bridge to HT or postoperatively for primary graft dysfunction (PGD). Little is known about wound complications of an arterial VA‐ECMO cannulation site which can be fatal. Methods: From 2009 to 2021, outcomes of 80 HT recipients who were supported with peripheral VA‐ECMO either preoperatively or postoperatively were compared based on the site of arterial cannulation: axillary (AX: N  = 49) versus femoral artery (FA: N  = 31). Results: Patients in the AX group were older (AX: 59 years vs. 52 years, p  = .006), and less likely to have extracorporeal cardiopulmonary resuscitation (0% vs. 12.9%, p  = .040). Survival to discharge (AX, 81.6% vs. FA. 90.3%, p  = .460), incidence of stroke (10.2% vs. 6.5%, p  = .863), VA‐ECMO cannulation‐related bleeding (6.1% vs. 12.9%, p  = .522), and arm or limb ischemia (0% vs. 3.2%, p  = .816) were comparable. ECMO cannulation‐related wound complications were lower in the AX group (AX, 4.1% vs. FA, 45.2%, p  < .001) including the wound infections (2.0% vs. 32.3%, p  < .001). In FA group, all organisms were gram‐negative species. In univariate logistic regression analysis, AX cannulation was associated with less ECMO cannulation‐related wound complications (Odds ratio, .23, p  < .001). There was no difference between cutdown and percutaneous FA insertion regarding cannulation‐related complications. Conclusions: Given the lower rate of wound complications and comparable hospital outcomes with femoral cannulation, axillary VA‐ECMO may be an excellent option in HT candidates or recipients when possible